Pengaruh Metode Latihan Wall Shooting dan Mata Tertutup terhadap Hasil Shooting Free Throw - -, Priyanto (Universitas Negeri Semarang, 2012)
This study aims to determine the effect of differences between training methods and the wall shooting blindfolded free throw shooting to result in a basketball game. The population in this study is a Member of the Student Activity Unit (UKM) basketball Unnes son who totaled 12 students, the sample in this study to include the entire population being sampled with a total sampling technique.The results showed: 1) The difference between the effect of training methods shooting wall with eyes closed against the method results in a free throw shooting basketball game with the results of F count> F table or 20.167> 5.318, with a mean value of wall shooting 6.67> 4.83 for eyes closed method. he conclusion of the study is 1) There is a difference between the effect of free throw shooting training method using wall shooting and eyes closed against the results of free throw shooting, the shooting method yields better wall instead of the closed eyes in free throw shooting at the basketball game.